Pengaruh Promosi Jabatan, Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Kabupaten Sintang - Munica, Prisilia Tiara; Dwiarti, Rina (Indonesian Journal Publisher, 2024)
This research aims to analyze the effect of job promotion. compensation, and work environment on employee job satisfaction at the Sintang Regency Regional Financial and Asset Management Agency. This research was conducted using a quantitative approach. The sample in this study was 39 respondents who were all permanent employees of the Regional Financial and Asset Management Agency of Sintang Regency, West Kalimantan. Data collection techniques in this research are questionnaires, document studies and interviews (Inteview). The results of the instrument test stated that the data in this study was proven to be valid and reliable. The results of this research prove that: (1) Job promotion has a positive and significant effect on job satisfaction at the Regional Financial and Asset Management Agency (BPKAD) of Sintang Regency. (2) Compensation does not have a significant effect on job satisfaction at the Regional Financial and Asset Management Agency (BPKAD) of Sintang Regency. (3) The work environment does not have a significant effect on job satisfaction at the Regional Financial and Asset Management Agency (BPKAD) of Sintang Regency. (4) Job promotion, compensation and work environment simultaneously have a positive and significant effect on job satisfaction of employees of the Regional Financial and Asset Management Agency (BPKAD) of Sintang Regency.